Rija Nagar (Cham New Year) rituals - Paulson, Dave (Zenodo (CERN European Organization for Nuclear Research), 2026)
Annual celebration of the new year among Cham communities in Vietnam. This two-day experience happens during the first month of the year (according to the Cham calendar, the Sakawi), and incorporates a number of ritual practices and ceremonial events where religious dignitaries communicate between the spiritual realm and the broader community to expel bad and unlucky things, and ensure a positive, productive new year as the rainy season begins.
Keywords: Realm; Traditional knowledge; Wet season; dept.ant

New reconstruction of DAN5 cranium (Gona, Ethiopia) supports complex emergence of Homo erectus - Baab, Karen; Kaifu, Yousuke; Freidline, Sarah; Rogers, Michael; Semaw, Sileshi (Nature Communications, 2025)
The African Early Pleistocene is a time of evolutionary change and techno-behavioral innovation in human prehistory that sees the advent of our own genus, Homo, from earlier australopithecine ancestors by 2.8-2.3 million years ago. This was followed by the origin and dispersal of Homo erectus sensu lato across Africa and Eurasia between ~ 2.0 and 1.1 Ma and the emergence of both large-brained (e.g., Bodo, Kabwe) and small-brained (e.g., H. naledi) lineages in the Middle Pleistocene of Africa. Here we present a newly reconstructed face of the DAN5/P1 cranium from Gona, Ethiopia (1.6-1.5 Ma) that, in conjunction with the cranial vault, is a mostly complete Early Pleistocene Homo cranium from the Horn of Africa. Morphometric analyses demonstrate a combination of H. erectus-like cranial traits and basal Homo-like facial and dental features combined with a small brain size in DAN5/P1. The presence of such a morphological mosaic contemporaneous with or postdating the emergence of the indisputable H. erectus craniodental complex around 1.6 Ma implies an intricate evolutionary transition from early Homo to H. erectus. This finding also supports a long persistence of small-brained, plesiomorphic Homo group(s) alongside other Homo groups that experienced continued encephalization through the Early to Middle Pleistocene of Africa. The origin and dispersal of Homo erectus, a long-lived and geographically widespread human ancestor, are unclear despite a rich fossil record. Here, the authors reconstruct the face from a Homo erectus cranium from Gona, Ethiopia, dated to 1.5-1.6 million years ago, providing insights into the evolutionary transition from early Homo to H. erectus.
Keywords: Crania; Early Pleistocene; Hominidae; Homo erectus; Human evolution; Pleistocene; Sensu; Skull; dept.ant

Imposed Form in the Early Acheulean? Evidence from Gona, Afar, Ethiopia - Stout, Dietrich; Liu, Cheng; Muller, Antoine; Rogers, Michael; Semaw, Sileshi (Journal of Archaeological Method and Theory, 2025)
Keywords: Acheulean; Ancient history; Anthropology; Archaeology; Early Stone Age; Ethnology; Geography; Handaxe; History; Large cutting tool; Lithic technology; Pick; Pleistocene; Shaping; Sociology; dept.ant

Seeking Transcendence: The Quest for Spirituality in an Age of Detachment - Manzella, Joseph C. (Routledge, 2025)
Seeking Transcendence examines the various paths taken by those who have detached themselves from their traditional, institutional religious roots but are seeking non-traditional paths to spiritual experiences. Called the “nones” or "non-affiliated" in popular mass media, these include a significant number of Western folks who maintain a belief in God or at least consider themselves “spiritual but not religious”. Each chapter of the book explores these trends with a specific theme, as well as a case study based on the author’s ethnographic observation of alternative spiritual communities and practices in North America and Western Europe. Ultimately, this book shows how contemporary alternatives to traditional institutional religion appeal to nones, presenting the relevance of new religious movements and more secular spiritual paths to transcendence.
Keywords: Philosophy; Psychoanalysis; Psychology; Theology; Transcendence (philosophy); dept.ant

Long-term hominin preference for the gallery forest edge: Insights from the Gona paleosols, Afar, Ethiopia - Stinchcomb, Gary E.; Rogers, Michael J.; Semaw, Sileshi (Quaternary Science Reviews, 2025)
The Gona Paleoanthropological Research Project area in the Afar Region of Ethiopia arguably contains one of the most complete records of archaeological sites anywhere in the world, from the earliest Oldowan dated to 2.6 Ma, to the Later Stone Age (LSA) dated to ca. 12-7 Ka. This makes Gona an ideal place to examine long-term trends in hominin-environment interaction. We revisited archaeological and hominin fossil sites at Gona and characterized the fossil soils using paleopedology and found evidence of paleo-Fluvisols, -Cambisols and -Vertisols. Greater than 70% of those archaeological sites spanning Oldowan to the Later Stone Age are found in buried paleosols with A-C and A-Bk-C paleosol profiles resembling modern-day Fluvisols or Fluvic Cambisols. Fluvisol morphology shows presence of bedding, incipient soil structure development and overprinting after burial. Stratigraphy and lithofacies show that these paleo-Fluvisols were proximal to the ancestral Awash River (Type I depositional system) or a distal fan channel (Type II depositional system). These data suggest that soil burial rates were rapid due to proximal flooding, where this would be a primary factor inhibiting soil development. This style of sedimentation and weathering resembles a narrow (5–10 m width) strip of land in a modern-day channel shelf and bar setting, separating the river from the adjacent gallery forest. A review of the literature shows that the frequent association of artifacts with paleo-Fluvisols may be prevalent throughout eastern Africa and indicates a long history of hominin reliance on a riverine ecosystem edge, proximal stream water and gallery forest resources within broader river valleys. The few older archaeological sites (e.g., Oldowan and Acheulian) found in/on more well-developed paleosols at Gona are an exception to this rule. These latter sites may hint at different land-use patterns and thus differing trajectories of hominin-environmental interactions. Because most paleosol studies at Gona and elsewhere in eastern Africa use paleo-Vertisols or other more well-developed calcareous soils to reconstruct paleoenvironment, there is a potential spatial and temporal decoupling between those well-studied paleosols and the more weakly-developed ones where archaeology is found.
Keywords: Archaeology; Artificial intelligence; Astronomy; Computer science; Enhanced Data Rates for GSM Evolution; Geography; Geology; Gona; Mathematics; Paleoecology; Paleontology; Paleosol; Physics; Preference; River corridors; Statistics; Term (time); dept.ant; peer-reviewed

Gona, Ethiopia: microcosm of the stone age - Rogers, Michael J.; Semaw, Sileshi; Stinchcomb, Gary E.; Quade, Jay; Levin, Naomi E.; Cauche, Dominique (Handbook of Pleistocene Archaeology of Afric, 2023)
The Gona paleoanthropological field project in the Afar region of Ethiopia has long been associated with the earliest Oldowan stone tools. However, over the last 20 years, ongoing research at Gona has expanded its contributions considerably, producing fossils of Ardipithecus kadabba, Ardipithecus ramidus, and Homo erectus, as well as additional archaeological evidence of the earliest Oldowan and early Acheulean. Moreover, in the last few years, the Gona team has turned its attention to the younger deposits exposed in its study area and discovered a surprising number of Middle Stone Age (MSA) and Later Stone Age (LSA) archaeological sites, mostly from the Late Pleistocene to the early-middle Holocene. While any sedimentary sequence is incomplete by virtue of episodic depositional and erosional events over time, we are struck by the relative completeness of the archaeological sequence at Gona (Quade et al., 2008). The hominin fossils attract deserved attention, but the Gona project may ultimately be best known for preserving arguably the most extensive, detailed, and continuous Stone Age or Paleolithic archaeological sequence in the world, all contained within a small 25 km × 10 km area, approximately half of the total project area.
Accepted: 2023-05-12T14:11:36Z
Keywords: dept.ant

Buzo or recycler: waste collecting as gift exchange in the context of a new waste regime - Skoczen, Kathleen N.; Caram Ibarra, Maria A (Practicing Anthropology, 2023)
The Dominican Republic (DR) experienced an economic boom related to tourism development over the last 30 years. Subsequently, consumption has increased, accompanied by an exponential growth in inorganic waste. Without adequate solid waste management, an environmental crisis has developed. Plastic waste litters roadsides, streets, streams, and beaches, threatening the very industry that enabled it. Informal waste collectors are on the front line of addressing, if not alleviating, the crisis but are regarded as marginal and inconsequential. A new waste regime is inevitable and imminent. Waste collectors are justifiably concerned that new systems may threaten their livelihoods. As such, they leverage their work, vis-à-vis a gift economy, to place themselves as essential to addressing the environmental crisis.
Keywords: dept.ant

The wastescapes of Samaná - Skoczen, Kathleen; Pantaleón, Natividad; Abreu, Daniel (Practicing Anthropology, 2023)
We conducted a formative research study on the peninsula of Samaná, in the northeast corner of the Dominican Republic, focused on how people viewed, categorized, and handled solid waste. With the passage of a new law, a motivated government administration is now addressing the solid waste crisis on the peninsula. Here, we examine some of the pre-existing attitudes about the solid waste of Samaná residents. Results from the study reveal that, contrary to many assumptions, local Dominicans are aware of the waste crisis and, in fact, are often depressed and anxious over it, even as they feel angry and helpless about how to resolve it. On closer examination and drawing on Appadurai’s theoretical framework of “-scapes,” we can understand that the waste crisis is not a local problem, and, as such, sustainable solutions need to include a broader effort to control plastic entering the environment.
Keywords: dept.ant

Language and racial capitalism: linguistic anthropological approaches to minoritized labor, standard language, and racial bias - McGill, Kenneth (Transforming Anthropology, 2023)
This article examines racial capitalism from a semiotic perspective, arguing that economic value, like language and race, can be described in situated and indexical terms. I attempt to show how raciolinguistic bias in and around the workplace is linked to a larger labor market in which minoritized labor is reproduced in a systemic way, and to explore hegemonic formations of racialization in the workplace and beyond. The jumping-off point for much of my argument is the work of the historian and political theorist Cedric Robinson.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/traa.12246
Keywords: dept.ant; labor; language; markets; minoritization; peer-reviewed; race

An Archaeological Perspective on Neocolonialism, Heritage-Making, and Historical Preservation at the Henry Whitfield House in Guilford, Connecticut - Farley, William; Mcbride, Michael; Chesler, Kevin; Godfrey, Jonathan; Pascale, Devin (Bulletin of the Archaeological Society of Connecticut, 2020)
Southern Connecticut State University conducted its first year of excavations at the Henry Whitfield State Museum in Guilford, Connecticut in July, 2018. This research was a continuation of nearly fifty years of intermittent archaeological research at the Whitfield Museum property. The 2018 field season was spent exploring a previously uninvestigated locus. While we did find some evidence of 17th, 18th, and 19th century activities at this locus, the most exciting finds were related to the neocolonial revival of the museum property in the first half of the 20th century. In addition to a general report on findings from the 2018 excavations, we explore the historical context of the Whitfield House in the late 19th and early 20th centuries, especially its perceived emblematic association with colonial English descendant communities in light of the period’s social anxieties about immigration, shifting racial dynamics, and economic and religious change.
Keywords: dept.ant; peer-reviewed; ⛔ No DOI found

Troops and Tribes: Masculinity, Playing Indian, and the Social Politics of Ernest Thompson Seton's Expulsion from the Boy Scouts of America - Farley, William (Connecticut History Review, 2021)
Keywords: dept.ant; peer-reviewed

The Wari Civilization and Their Descendants: Imperial Transformation in Pre-Inca Cuzco - Glowacki, Mary; McEwan, Gordon Francis (Lexington Books, 2021)
"Drawing on research conducted in Cuzco, Peru, The Wari Civilization and Their Descendants: Imperial Transformation in Pre-Inca Cuzco analyzes the political and social transformations that led to the downfall of the Wari civilization in the Andean Middle Horizon period (AD 500-1000) and resulted in the rise of the Inca state."–
Keywords: Antiquities; Antiquities; Excavations (Archaeology); Cusco (Region); Indians of South America; Cusco (Region); Pikillacta Site (Peru); Cusco (Peru : Region); Cuzco; History; Huari pottery; Huari Indians; Peru; Politics and government; Huari Indians; dept.ant; faculty_collection

Rising tensions: heritage-tourism development and the commodification of “Authentic” culture among the Cham community of Vietnam - Quang, Tuyen D.; Noseworthy, William B.; Paulson, Dave (Cogent Social Sciences, 2022)
This study examines the complexities of cultural-heritage management in Vietnam and the various tensions that arise within initiatives promoting “authentic” versions of cultural practice. In particular, this research investigates local perceptions concerning the commodification of the Cham New Year (Rija Nâgar) at temple-tower complexes, and explores the implications of sacred religious holidays (ngày lễ) that are organized as festival (lễ hội) events. Arranged by local Vietnamese officials, the implementation of these events for tourists contradicts important Cham worldviews, leading to negative perceptions of tourism among community members, and fears that such practices pose irrevocable damage for Cham spirituality and the future of their ancestral heritage. This research underscores the importance of community involvement with respect to decision making in cultural-heritage management, and that heritage tourism in Vietnam, and Southeast Asia more generally, may be dramatically improved with guidance from indigenous voices and local spiritual leaders.
4 citations (Crossref) [2023-10-31] _eprint: https://doi.org/10.1080/23311886.2022.2116161
Keywords: Cham; Heritage tourism; Vietnam; cultural commodification; dept.ant; indigenous participation; peer-reviewed; sacred space

Fluvial response to Quaternary hydroclimate in eastern Africa: Evidence from Gona, Afar, Ethiopia - Stinchcomb, Gary E.; Quade, Jay; Levin, Naomi E.; Iverson, Nels; Dunbar, Nelia; McIntosh, William; Arnold, Lee J.; Demuro, Martina; Duval, Mathieu; Grün, Rainer; Zhao, Jian-xin; White, Marie; et al. (Quaternary Science Reviews, 2023)
The Busidima Formation in the Afar region, Ethiopia, spans the Quaternary and records the cultural evolution of the genus Homo. Yet, the Middle Pleistocene to Holocene fluvial environments in which early humans lived are undersampled in eastern Africa. This paper examines the stratigraphy, geochronology and paleoenvironments of the newly designated Odele Member of the uppermost Busidima Formation (<152 thousand years ago (ka)), which has received little attention despite representing a critical period in the evolution of early Homo sapiens and its migration out of Africa. The Odele Member is 40–50 m thick and is dated using tephrochronology, radiometric, luminescence, and electron spin resonance techniques. The member spans 151 to 7 ka, defined at the base by the widespread Waidedo Vitric Tuff (WAVT, 151 ± 16 ka modeled age and 95.4% credible interval - C.I.). There are two prominent erosional unconformities in the Odele Member, a lower one after the WAVT deposition with a modeled 95.4% C.I. range of 124–97 ka; and an upper one involving widespread alluvial fan incision commencing between 21.7 and 12.9 ka. The uppermost Odele Member also contains black, organic-rich mats, redox features, reed casts, and freshwater gastropods marking wetter conditions during the terminal Pleistocene and Early Holocene. A black, fine-grained relict soil coeval with the Halalalee paleosol bounds the top of the Odele Member and has mollic and vertic properties, weathering since ∼12 ka. These incision events and prominent paleosol development near/at the top of the Busidima Formation document Middle to Late Pleistocene Awash River incision to its present-day course. Paleo-rainfall estimates suggest that the Early Holocene-age Halalalee paleosol weathered under a climate with mean annual rainfall 10–15% higher than today. A compilation of radiocarbon ages from aquatic gastropods, carbonized wood and charcoal from the upper Odele Member shows wetter and possibly more vegetated conditions during late marine isotope stage (MIS) 3 and the African Humid Period (AHP) that are tightly coupled with precession-driven summer insolation maxima. These key findings suggest that periods of incision, aggregation, and landscape stability in the Odele Member have an orbital precession pacing. The Odele Member revises upward the age of the Busidima Formation to 7 ka, showing that it spans into the Holocene and now includes Middle and Later Stone Age archaeological traditions.
0 citations (Crossref) [2023-10-31]
Keywords: Electron spin resonance; Ethiopian rift; Fluvial aggradation; Fluvial incision; Paleosol; Radiocarbon; Tephrochronology; U-series; dept.ant; pIR-IRSL; peer-reviewed

The endocast from Dana Aoule North (DAN5/P1): A 1.5 million year-old human braincase from Gona, Afar, Ethiopia - Bruner, Emiliano; Holloway, Ralph; Baab, Karen L.; Rogers, Michael J.; Semaw, Sileshi (American Journal of Biological Anthropology, 2023)
The nearly complete cranium DAN5/P1 was found at Gona (Afar, Ethiopia), dated to 1.5–1.6 Ma, and assigned to the species Homo erectus. Its size is, nonetheless, particularly small for the known range of variation of this taxon, and the cranial capacity has been estimated as 598 cc. In this study, we analyzed a reconstruction of its endocranial cast, to investigate its paleoneurological features. The main anatomical traits of the endocast were described, and its morphology was compared with other fossil and modern human samples. The endocast shows most of the traits associated with less encephalized human taxa, like narrow frontal lobes and a simple meningeal vascular network with posterior parietal branches. The parietal region is relatively tall and rounded, although not especially large. Based on our set of measures, the general endocranial proportions are within the range of fossils included in the species Homo habilis or in the genus Australopithecus. Similarities with the genus Homo include a more posterior position of the frontal lobe relative to the cranial bones, and the general endocranial length and width when size is taken into account. This new specimen extends the known brain size variability of Homo ergaster/erectus, while suggesting that differences in gross brain proportions among early human species, or even between early humans and australopiths, were absent or subtle.
2 citations (Crossref) [2023-10-31] _eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1002/ajpa.24717
Keywords: Homo erectus; Homo ergaster; Lower Pleistocene; brain evolution; dept.ant; human evolution; paleoneurology; peer-reviewed

Language and economic value: A multimodal approach - McGill, K. (Language Sciences, 2022)
This article presents an approach to economic value based on the paradigm of multimodal analysis. I argue that economic value is constituted within its own interactional mode, that economic laws are constituted as semiotic resources, and that markets can ultimately be understood as the “habituation in mode” (Kress) of these resources. The article is organized as a set of problems and possible solutions for the multimodal analysis of language and value. © 2022 Elsevier Ltd
0 citations (Crossref) [2023-10-31] tex.art_number: 101462 tex.author_keywords: Economic value; Language; Multimodal analysis; Semiotic resources tex.document_type: Article tex.source: Scopus
Keywords: dept.ant; peer-reviewed

Health, Diet, and Violence during Wari Expansion: Bioarchaeology at Ak’awillay, Cusco, Peru - Bey, Bridget C.; Andrushko, Valerie A.; Bélisle, Véronique (Ñawpa Pacha, 2021)
The expansion of states and empires often has important consequences for local populations, including increased violence, greater stress, or dietary modifications resulting in changing health conditions. This paper presents the analysis of 73 skeletons from the Cusco site of Ak’awillay, shedding light on diet, health, and violence in the Middle Horizon. Results indicate that the people of Ak’awillay led a rigorous lifestyle and suffered from more nutritional deficiencies compared to previous populations, possibly pointing to increased maize consumption. However, the low incidence of trauma at Ak’awillay and other Cusco sites suggest that the Wari presence in Cusco was not entrenched in violence.
2 citations (Crossref) [2023-10-31] _eprint: https://doi.org/10.1080/00776297.2021.1878602
Keywords: Horizonte Medio; Human remains; Middle Horizon; Wari; burials; dept.ant; diet; dieta; entierros; health; peer-reviewed; restos humanos; salud; violence; violencia

Reconstruction and analysis of the DAN5/P1 and BSN12/P1 Gona Early Pleistocene Homo fossils - Baab, Karen L.; Rogers, Michael; Bruner, Emiliano; Semaw, Sileshi (Journal of Human Evolution, 2022)
Two Early Pleistocene fossils from Gona, Ethiopia, were originally assigned to Homo erectus, and their differences in size and robusticity were attributed to either sexual dimorphism or anagenetic evolution. In the current study, we both revisit the taxonomic affinities of these fossils and assess whether morphological differences between them reflect temporal evolution or sexual variation. We generated virtual reconstructions of the mostly complete ∼1.55 Ma DAN5/P1 calvaria and the less complete 1.26 Ma BSN12/P1 fossil, allowing us to directly compare their anterior vault shapes using landmark-based shape analysis. The two fossils are similar in calvaria shape to H. erectus and also to other Early Pleistocene Homo species based on a geometric morphometric analysis of calvaria landmarks and semilandmarks. The DAN5/P1 fossil bears a particularly close affinity to the Georgian H. erectus fossils and to KNM-ER 1813 (H. habilis), probably reflecting allometric influences on vault shape. Combined with species-specific traits of the neurocranium (e.g., midline keeling, angular torus), we confirm that these fossils are likely early African H. erectus. We calculated regression-based estimates of endocranial volume for BSN12/P1 of 882–910 cm3 based on three virtual reconstructions. Although BSN12/P1 is markedly larger than DAN5/P1 (598 cm3), both fossils represent the smallest adult H. erectus known from their respective time periods in Africa. Some of the difference in endocranial volume between the two Gona fossils reflects broader species-level brain expansion from 1.77 to 0.01 Ma, confirmed here using a large sample (n = 38) of H. erectus. However, shape differences between these fossils did not reflect species-level changes to calvaria shape. Moreover, the analysis failed to recover a clear pattern of sexually patterned size or shape differences within H. erectus based on our current assessments of sex for individual fossils.
5 citations (Crossref) [2023-10-31]
Keywords: Africa; Animals; Biological Evolution; Brain; Brain evolution; Calvaria shape; Ethiopia; Fossils; Hominidae; Homo erectus; Intraspecific variation; Pleistocene; Sexual dimorphism; Skull; anatomy and histology; animal; brain; dept.ant; evolution; fossil; hominid; human evolution; intraspecific variation; morphology; peer-reviewed; reconstruction; sexual dimorphism; skull; temporal evolution

Canine sexual dimorphism in Ardipithecus ramidus was nearly human-like. - Suwa; Sasaki, Tomohiko; Semaw, Sileshi; Rogers, Michael J.; Simpson, Scott W.; Kunimatsu, Yutaka; Nakatsukasa, Masato; Kono, Reiko T.; Zhang, Yingqi; Beyene, Yonas; Asfaw, Berhane; White, Tim D. (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Body and canine size dimorphism in fossils inform sociobehavioral hypotheses on human evolution and have been of interest since Darwin’s famous reflections on the subject. Here, we assemble a large dataset of fossil canines of the human clade, including all available Ardipithecus ramidus fossils recovered from the Middle Awash and Gona research areas in Ethiopia, and systematically examine canine dimorphism through evolutionary time. In particular, we apply a Bayesian probabilistic method that reduces bias when estimating weak and moderate levels of dimorphism. Our results show that Ar. ramidus canine dimorphism was significantly weaker than in the bonobo, the least dimorphic and behaviorally least aggressive among extant great apes. Average male-to-female size ratios of the canine in Ar. ramidus are estimated as 1.06 and 1.13 in the upper and lower canines, respectively, within modern human population ranges of variation. The slightly greater magnitude of canine size dimorphism in the lower than in the upper canines of Ar. ramidus appears to be shared with early Australopithecus, suggesting that male canine reduction was initially more advanced in the behaviorally important upper canine. The available fossil evidence suggests a drastic size reduction of the male canine prior to Ar. ramidus and the earliest known members of the human clade, with little change in canine dimorphism levels thereafter. This evolutionary pattern indicates a profound behavioral shift associated with comparatively weak levels of male aggression early in human evolution, a pattern that was subsequently shared by Australopithecus and Homo. © 2021 National Academy of Sciences. All rights reserved.
4 citations (Crossref) [2023-10-31]
Keywords: Animals; Australopithecus; Bayes Theorem; Bayes theorem; Biological Evolution; Cuspid; Ethiopia; Female; Fossils; Hominidae; Humans; Male; Models; Pan paniscus; Phylogeny; Sex Characteristics; Theoretical; adult; aggression; anatomy and histology; animal; article; canine tooth; cladistics; classification; dept.ant; evolution; female; fossil; hominid; human; male; mandibular canine; maxillary canine; nonhuman; peer-reviewed; phylogeny; sex difference; sexual characteristics; theoretical model

Estimating sexual size dimorphism in fossil species from posterior probability densities - Sasaki, Tomohiko; Semaw, Sileshi; Rogers, Michael J.; Simpson, Scott W.; Beyene, Yonas; Asfaw, Berhane; White, Tim D.; Suwa (Proceedings of the National Academy of Sciences of the United States of America, 2021)
Accurate characterization of sexual dimorphism is crucial in evolutionary biology because of its significance in understanding present and past adaptations involving reproductive and resource use strategies of species. However, inferring dimorphism in fossil assemblages is difficult, particularly with relatively low dimorphism. Commonly used methods of estimating dimorphism levels in fossils include the mean method, the binomial dimorphism index, and the coefficient of variation method. These methods have been reported to overestimate low levels of dimorphism, which is problematic when investigating issues such as canine size dimorphism in primates and its relation to reproductive strategies. Here, we introduce the posterior density peak (pdPeak) method that utilizes the Bayesian inference to provide posterior probability densities of dimorphism levels and within-sex variance. The highest posterior density point is termed the pdPeak. We investigated performance of the pdPeak method and made comparisons with the above-mentioned conventional methods via 1) computergenerated samples simulating a range of conditions and 2) application to canine crown-diameter datasets of extant known-sex anthropoids. Results showed that the pdPeak method is capable of unbiased estimates in a broader range of dimorphism levels than the other methods and uniquely provides reliable interval estimates. Although attention is required to its underestimation tendency when some of the distributional assumptions are violated, we demonstrate that the pdPeak method enables a more accurate dimorphism estimate at lower dimorphism levels than previously possible, which is important to illuminating human evolution. © 2021 National Academy of Sciences. All rights reserved.
2 citations (Crossref) [2023-10-31]
Keywords: Animals; Bayes Theorem; Bayes theorem; Cuspid; Female; Fossils; Male; Models; Sex Characteristics; Statistical; animal; article; attention; canine tooth; controlled study; dept.ant; female; fossil; human; human experiment; intermethod comparison; male; nonhuman; peer-reviewed; primate; probability; sex difference; sexual characteristics; statistical model

Paleoenvironments of Gona, Ethiopia, between 3-1 Mya: Evidence from faunal analysis - Leiss, Amanda C.; Rogers, Michael J.; Semaw, Sileshi (American Journal of Physical Anthropology, 2020)
WOS:000513288902015
Keywords: dept.ant; peer-reviewed; ⛔ No DOI found

Health in the Inca heartland: A paleopathological analysis of burials from the Cuzco region of Peru - Andrushko, Valerie A. (International Journal of Osteoarchaeology, 2021)
While much is known about the rise and expansion of the Inca Empire (AD 1438–1532) throughout the Andean region of South America, the health effects of the empire in its capital region remain unclear. The present study addresses the Inca Empire's impact on health in the Cuzco region of Peru through an analysis of four conditions (dental enamel hypoplasias, cribra orbitalia, porotic hyperostosis and periosteal lesions) in 929 pre-Inca and Inca burials. The study results show little change in health from the Late Intermediate Period (AD 1000–1438) to the Inca Imperial Period (AD 1438–1532). When the location of the Inca burial sites was analysed, individuals from sites closest to the centre of the empire's capital showed lower frequencies in pathological conditions compared with individuals from sites in the countryside. These results suggest that individuals centred in the Inca imperial sphere benefited from their position and experienced better health. A similar finding was also seen with the previous Wari occupation of Cuzco in the Middle Horizon (AD 600–1000), as burials within the Wari imperial sphere exhibited fewer non-specific stress indicators than those outside of it. Overall, the frequencies of pathological conditions in the Cuzco region, which ranged from 4.6% for porotic hyperostosis to 18.8% for periosteal lesions, were lower than frequencies from many coastal Peruvian sites. These differences may relate to a diverse diet provided by the Cuzco region ecosystem, as well as the absence of ecological challenges that affected coastal populations. © 2021 John Wiley & Sons, Ltd.
4 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85103956435
Keywords: dept.ant; peer-reviewed

Hybrid methods for locating and excavating early historical conflict-related domestic sites - Farley, William A.; McBride, Kevin A.; Willison, Megan K. (Historical Archaeology, 2021)
Since 2012, the Mashantucket Pequot Museum and Research Center in Mashantucket, Connecticut, in collaboration with the University of Connecticut, has carried out a research program to survey and document the battlefields of the Pequot War (1636–1637). The unique nature of the project has required the refinement of the long-standing field methods of battlefield archaeology. In this article, we argue that these techniques, while originally developed to explore sites of conflict, can be operationalized to locate 17th-century indigenous domestic sites. We describe this modified method and provide a site-specific case study to present its efficacy. © 2021, Society for Historical Archaeology.
1 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85103623906
Keywords: dept.ant; peer-reviewed

Revelations of ancient head shape: Cranial modification in the Cuzco region of Peru, Early Horizon to Inca Imperial Period - Andrushko, V.A. (American Journal of Physical Anthropology, 2021)
Objectives: Cranial vault modification (CVM), the intentional reshaping of the head, indicated group affiliation in prehistoric Andean South America. This study aims to analyze CVM data from the Cuzco region of Peru to illuminate patterns of early migration and settlement along with the later impact of the Inca Empire (AD 1438–1532) on the ethnic landscape. Materials and Methods: 419 individuals from 10 archaeological sites spanning over 2300 years were assessed for CVM using morphological analysis. Results: CVM patterns show distinct temporal attributes: the tabular type of modification appeared first and dominated the early sample (900 BC–AD 600), followed by an influx of unmodified crania during the Middle Horizon (AD 600–1000). The annular type appeared later during the Late Intermediate Period (AD 1000–1438). In the subsequent period of Inca imperialism, modification rates were higher at sites in the Cuzco countryside than in Cuzco city sites. Discussion: The study results, combined with archaeological and ethnohistoric data, reveal the sociopolitical transformations that occurred prior to and during the rise of the Inca Empire. The influx of unmodified crania during the Middle Horizon resulted at least partly from Wari occupation, while the appearance of the annular type during the LIP points to migration into the area, possibly from the Lake Titicaca region. In the Inca Imperial Period, Inca individuals at Cuzco city sites refrained from modification as a sign of their ethnic identity, while modification patterns in the Cuzco countryside likely reflect state-coerced resettlement of different ethnic groups. © 2020 Wiley Periodicals LLC.
3 citations (Crossref) [2023-10-31] Type: Article tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85097844845
Keywords: 15th Century; American Indian; Ancient; Archaeology; Body Modification; Female; History; Human Migration; Humans; Indians; Male; Medieval; Non-Therapeutic; Peru; Skull; South American; adult; archeology; article; body modification; controlled study; dept.ant; ethnic group; ethnology; female; history; human; human experiment; major clinical study; male; migration; occupation; pathology; peer-reviewed; skull

Review of" Indigenous Persistence in the Colonized Americas: Material & Documentary Perspectives on Entanglement" - Farley, William A. (Historical Archaeology, 2020)
0 citations (Crossref) [2023-10-31]
Keywords: book.review; dept.ant; peer-reviewed

Language, labor and reification - McGill, Kenneth (Language Sciences, 2020)
In this article, I attempt to describe how language is reified, using the call center as an extended example. I take up recent debates regarding language and economic value, attempting to disentangle a by now substantial series of arguments about language and commodification. The theoretical core of the paper is drawn from the work of Georg Lukács, who provided the account of reification that was at the root of twentieth century critical theory. Following Lukács, I argue that what is indispensable in the process of reification is both a “contemplative stance” in relation to economic laws and the presence of “special partial systems” within the production process of commodities. These are particularly important considerations for what I refer to as the one-sided rationalization of language that occurs in call centers in particular, but also on a more widespread social basis. © 2020 Elsevier Ltd
0 citations (Crossref) [2023-10-31] WOS:000541167600006
Keywords: Commodity; Consciousness; Economic value; Language; Reification; dept.ant; peer-reviewed

Fossil Cercopithecidae from the Early Pliocene Sagantole Formation at Gona, Ethiopia - Frost, Stephen R.; Simpson, Scott W.; Levin, Naomi E.; Quade, Jay; Rogers, Michael J.; Semaw, Sileshi (Journal of Human Evolution, 2020)
The Early Pliocene Sagantole Fm. in the Gona Project area, Afar State, Ethiopia, is noted for discoveries of the early hominin Ardipithecus ramidus. A large series of fossil cercopithecid primates dated to between 4.8 and 4.3 Ma has also been collected from these sediments. In this paper, we use qualitative analysis and standard dental and postcranial measures to systematically describe the craniodental remains and tentatively allocate postcrania to taxa where we are able to. We then use these data to compare these specimens to fossil assemblages from contemporary sites, interpret their paleobiology, and discuss implications for the paleoecology of the Gona Sagantole Fm. We recognize three cercopithecid species in the Gona Sagantole Fm. Pliopapio alemui makes up approximately two-thirds of the identifiable specimens; nearly all of the rest are allocated to Kuseracolobus aramisi, and a single molar indicates the presence of a second, somewhat larger but morphologically distinct papionin. Among the Early Pliocene cercopithecids from Gona are also a number of postcranial elements. None of the postcranial remains are directly associated with any of the cranial material. Nonetheless, some of the distal humeri and proximal femora can be tentatively allocated to either Pl. alemui or K. aramisi based on a combination of size, as the latter is approximately 50% larger than the former, and morphology. If these assignments are correct, they suggest K. aramisi was primarily arboreal and similar to most extant colobines, whereas Pl. alemui was more mixed in its substrate use, being more terrestrially adapted than K. aramisi, but less so than extant Papio or Theropithecus. Thus, we interpret the predominance of Pl. alemui over K. aramisi is consistent with a somewhat more open environment at Gona than at Aramis. © 2020 Elsevier Ltd
5 citations (Crossref) [2023-10-31] tex.ids: Rogers2020, frostFossilCercopithecidaeEarly2020a tex.citation: https://api.elsevier.com/content/abstract/scopus_id/85085551825 type: Article
Keywords: Animals; Ardipithecus ramidus; Cercopithecidae; Ethiopia; Female; Fossils; Gona; Kuseracolobus; Life History Traits; Male; Paleobiology; Papio; Pliocene; Pliopapio; Primates; Theropithecus; anatomy and histology; animal; cranium; dentition; dept.ant; female; fossil; fossil assemblage; hominid; life history trait; male; paleobiology; paleoecology; peer-reviewed; physiology; qualitative analysis; taxonomy

Paleoenvironmental changes during the last 6 million years at Gona, Afar Region, Ethiopia - Levin, Naomi E; Simpson, S.; Rogers, Michael J.; Semaw, S. (African Paleoecology and Human Evolution, 2020)
Keywords: dept.ant

Co-occurrence of Acheulian and Oldowan artifacts with Homo erectus cranial fossils from Gona, Afar, Ethiopia. - Semaw, Sileshi; Rogers, Michael J; Simpson, Scott W; Levin, Naomi E; Quade, Jay; Dunbar, Nelia; McIntosh, William C; Caceres, Isabel; Stinchcomb, Gary E; Holloway, Ralph L; Brown, Francis H; Butler, Robert F; et al. (Science advances, 2020)
Although stone tools generally co-occur with early members of the genus Homo, they are rarely found in direct association with hominins. We report that both Acheulian and Oldowan artifacts and Homo erectus crania were found in close association at 1.26 million years (Ma) ago at Busidima North (BSN12), and ca. 1.6 to 1.5 Ma ago at Dana Aoule North (DAN5) archaeological sites at Gona, Afar, Ethiopia. The BSN12 partial cranium is robust and large, while the DAN5 cranium is smaller and more gracile, suggesting that H. erectus was probably a sexually dimorphic species. The evidence from Gona shows behavioral diversity and flexibility with a lengthy and concurrent use of both stone technologies by H. erectus, confounding a simple "single species/single technology" view of early Homo. Copyright © 2020 The Authors, some rights reserved; exclusive licensee American Association for the Advancement of Science. No claim to original U.S. Government Works. Distributed under a Creative Commons Attribution NonCommercial License 4.0 (CC BY-NC).
40 citations (Crossref) [2023-10-31] Place: United States Semaw, Sileshi. Centro Nacional de Investigacion sobre la Evolucion Humana (CENIEH), Sierra de Atapuerca 3, 09002 Burgos, Spain. Semaw, Sileshi. Stone Age Institute and CRAFT Research Center, 1392 W. Dittemore Rd., Gosport, IN 47408, USA. Rogers, Michael J. Department of Anthropology, Southern Connecticut State University, 501 Crescent Street, New Haven, CT 06515, USA. Simpson, Scott W. Department of Anatomy, Case Western Reserve University School of Medicine, Cleveland, OH 44106, USA. Simpson, Scott W. Laboratory of Physical Anthropology, Cleveland Museum of Natural History, Cleveland, OH 44106, USA. Levin, Naomi E. Department of Earth and Environmental Sciences, University of Michigan, 1100 North University Avenue, Ann Arbor, MI 48109, USA. Quade, Jay. Department of Geosciences/Desert Laboratory, University of Arizona, Tucson, AZ 85721, USA. Dunbar, Nelia. New Mexico Bureau of Geology and Mineral Resources, Earth and Environmental Science Department, New Mexico Tech, 801 Leroy Place, Socorro, NM 87801-4796, USA. McIntosh, William C. New Mexico Bureau of Geology and Mineral Resources, Earth and Environmental Science Department, New Mexico Tech, 801 Leroy Place, Socorro, NM 87801-4796, USA. Caceres, Isabel. Universitat Rovira i Virgili (URV), Avinguda de Catalunya 35, 43002 Tarragona, Spain. Caceres, Isabel. IPHES, Institut Catala de Paleoecologia Humana i Evolucio Social, Zona Educacional 4-Campus Sescelades URV (Edifici W3), 43007 Tarragona, Spain. Stinchcomb, Gary E. Watershed Studies Institute and Department of Earth and Environmental Sciences, Murray State University, Murray, KY 42071, USA. Holloway, Ralph L. Department of Anthropology, Columbia University, 1200 Amsterdam Ave., New York, NY 10027, USA. Brown, Francis H. The University of Utah, 201 South Presidents Circle Room 201, Salt Lake City, UT 84112, USA. Butler, Robert F. Department of Physics, University of Portland, Portland, OR 97203, USA. Stout, Dietrich. Department of Anthropology, Emory University, 1557 Dickey Drive, Atlanta, GA 30322, USA. Everett, Melanie. Chevron Energy Technology Company, 1500 Louisiana St., Houston, TX 77002, USA.
Keywords: *Biological Evolution; *Fossils; *Hominidae; *Skull/ah [Anatomy & Histology]; Animals; Archaeological site; Behavioral diversity; Biodiversity; Biological Evolution; Co-occurrence; Ethiopia; Fossils; Hominidae; Hominidae/ah [Anatomy & Histology]; Hominidae/cl [Classification]; Hominins; Homo erectus; Humans; Paleontology; Single species; Skull; anatomy and histology; animal; classification; dept.ant; evolution; fossil; hominid; human; paleontology; peer-reviewed; skull

The bioarchaeology of Wari collapse in Cuzco, Peru: A study of health and trauma from the Middle Horizon-Late Intermediate Period transition at Cotocotuyoc - Andrushko, Valerie (The Wari Civilization and Their Descendants: Imperial Transformation in Pre-Inca Cuzco, 2020)
Drawing on research conducted in Cuzco, Peru, The Wari Civilization and Their Descendants: Imperial Transformation in Pre-Inca Cuzco, Peru analyzes the political and social transformations that led to the downfall of the Wari civilization in the Andean Middle Horizon period (AD 500–1000) and resulted in the rise of the Inca state. The contributors to this collection present evidence of the Wari civilization’s robust, imperialistic occupation of Cuzco, and argue that this presence laid the groundwork for later regional polities that can be traced to the Late Horizon Inca period (AD 1476–1532). This collection fills a gap in scholarly literature on Cuzco prehistory, the provincial southern highlands of the Wari civilization, and early imperialism in the Andes.
Keywords: dept.ant